Carbon source utilization in hybrid Shiga toxin-producing and uropathogenic Escherichia coli indicates uropathogenic origin - Imke Johanna Temme; Petya Berger; Ulrich Dobrindt; Alexander Mellmann (International Journal of Medical Microbiology)
To investigate the adaptation of hybrid Escherichia coli to the intestinal and extraintestinal milieu, we compared our model hybrid Shiga toxin-producing (STEC) and uropathogenic (UPEC) E. coli O2:H6 strains with non-pathogenic E. coli and canonical UPEC and STEC strains in a carbon source utilization assay testing 95 common carbon sources under aerobic and anaerobic conditions. Comparison of anaerobic to aerobic growth showed a 2-fold decrease and 2.5-fold increase in the growth capacity and lag phase, respectively. While the UPEC and STEC/UPEC hybrids retained the utilization of several organic acids, amino acids, and peptides, the STEC and non-pathogenic strains relied almost exclusively on the utilization of sugar compounds under anaerobic conditions. Cluster analysis indicated a higher degree of difference and separation between all strains under aerobic conditions. The UPEC, hybrids, and STEC strain B2F1 showed high similarities in aerobic carbon utilization following growth patterns observed in previous phenotype assays. Additionally, we observed known UPEC virulence traits, such as the aerobic utilization of D-serine in our model STEC/UPEC hybrids. Combined, these findings suggest that the intestinal STEC/UPEC O2:H6 isolates originated from a UPEC background and acquired the ability to cause intestinal disease with the addition of Shiga toxin as a virulence factor.